PENGARUH KEADILAN, MORAL, E-FILLING, E-BILLING TERHADAP KEPATUHAN PAJAK MELALUI KEPUASAN WAJIB PAJAK - Ying, Win; Ngadiman, Ngadiman (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This research aims to find out how the influence of tax justice, morals, the application of e-filling and e-billing to tax compliance through taxpayer satisfaction in Jakarta. The samples were selected by purposive sampling method and used primary data by distributing questionnaires to 120 taxpayers. This data processing is assisted by the Smart PLS 3.0 program. The results of this study show that tax justice and morale have a positive influence on tax compliance. e-filling and e-billing variables positively affect tax compliance through satisfaction levels but on the other hand the study found that e-filling and e-billing variables did not have a positive influence on taxpayer compliance. The implication of this research is that it is necessary to improve tax services so that taxpayer compliance can also increase.